EFFECT OF VARIOUS DACTYLIFERA MALES POLLINIZER ON POMOLOGICAL TRAITS AND ECONOMICAL YIELD INDEX OF CV’S SHAKRI, ZAHIDI AND DHAKKI DATE PALM (PHOENIX DACTYLIFERA L.) - M. Iqbal; M. Niamatullah; M. Munir (Journal of Animal and Plant Sciences, 2012)
A study was aimed at determining the effect of different Dactylifera male pollinizer on the pomological traits of Shakri, Zahidi and Dhakki Date Palm i.e. fruit set, days to fruit set, fruit characteristics, fruit drop and economical yield index during two successive seasons (February to September) in 2005 and 2006 at the experimental Date Palm Orchard of Gomal University Dera Ismail Khan. Results indicated that fruit setting percentage and days to fruit setting were significantly affected by male pollinizer in both years of study. Similarly fruit characteristics like fruit weight, length, breadth and seed weight was also significantly affected. The pulp weight was significantly affected in 2005, where no significant difference was observed in 2006. Maximum fruit drop percentage in cv. Dhakki was recorded as 39.00 and 38.53 during 2005 and 2006 respectively. M1 pollen yielded the maximum fruits as 5.27 kg and 5.00 kg bunch-1 in 2005 and 2006 respectively. It can be concluded from the results that selection of suitable male parent as male pollinizer from different date cultivars resulted in improving quality of date varieties. Maximum fruit setting was recorded in Zahidi and Shakri while fruit characteristics like fruit weight, length, breadth and weight of pulp was recorded in cv. Dhakki. Similarly maximum fruit drop and economical yield was observed in Dhakki. It can be further concluded that amongst date palm varieties, Dhakki produced economical yield under the agro climatic conditions of Dera Ismail Khan.
Keywords: Date palm; Dactylifera; Male pollinizers; Female varieties.